A PRELIMINARY EXPLORATION of BLUE ECONOMY DEVELOPMENT and GOVERNANCE MODELS in TAIWAN’S OFFSHOR ISLANDS - Kan-Chung Huang; Yu-Ting Hung; Chao-Li Tai; Ching-Yun Lee (Graduate Program of Universitas Tarumanagara, 2026)
As the blue economy has become a key discourse in island and marine development, addressing marine use conflicts and governance demands while promoting economic activities has emerged as a critical issue. This study focuses on six major inhabited offshore islands in Taiwan, analyzing their blue economy development characteristics and corresponding marine governance responses. This research integrates institutional analysis and local perspectives through literature review and in-depth interviews, thereby supplementing gaps in existing studies. The findings reveal significant variations among the islands in terms of ecological carrying capacity, functional overlap of marine uses, and industrial development, forming a diverse spectrum ranging from low-density livelihood-oriented use to high-density tourism-oriented utilization. These differences reflect the contextual characteristics of their social-ecological systems. Further analysis indicates a strong correlation between blue economy development patterns and marine governance approaches. Livelihood-oriented islands tend to adopt low-impact marine use strategies, tourism-oriented islands emphasize intensity regulation, while diversifying or transitional islands require coordination among multiple marine use demands. This suggests that marine governance in offshore islands is highly context-specific rather than governed by a single institutional framework. Through cross-island comparison, this study develops a typological analytical framework that serves as an intermediary tool linking social-ecological differences with governance practices, contributing to a deeper understanding of the diversity of blue economy development in offshore islands.